Adaptación psicosocial del paciente oncológico ingresado y del familiar cuidador principal - Abián, Lidia; Cortés Funes, Hernán; Cortés Funes, Fabiola (Psicooncología, 2003)
The present study looks for the relation between the psychosocial distress experienced by the patient and his family caregiver during the period he is hospitalised. The sample is composed by 94 persons (oncology patients and family caregivers). We have used a sociodemographic questionnaire, the Hospital Anxiety and Depression Scale, the “Quality of life Questionnaire” for general satisfaction and social support and the family APGAR for family functioning. The results indicate that the anxiety of the caregiver is significantly higher than the one of the patient. The family functioning perceived by the patient correlates negatively with the depression and positively with the general satisfaction of the family caregiver. We found a correlation between the age and the depression subscale. In the family caregivers group we confirm that the higher scores in depression appear in ages between 35 and 55. Married patients and caregivers obtain higher punctuation in depression compared to unmarried ones. We conclude that the patients psychosocial distress differs from the caregivers distress. The psychological intervention should focus on the individual needs of the patient and the caregiver by promoting the social net of the relatives, supplying a better communication with the patient, reducing the caregivers anxiety and attending the demands derived from physical condition, marital status and age.